КРАТКОЕ ИЗЛОЖЕНИЕ ФОНЕТИКИ И ЛЕКСИКОЛОГИИ ТЮРКСКИХ ЯЗЫКОВ. - Вусала Асадова, (Research Focus International Scientific Journal, 2024)
The article examines the general grammatical structure of modern Turkish languages. In the study, the phonetic structure and lexical units of Turkish languages ​​were compared, and common and different features of phonemes were compared. At the same time, vowel sounds of Turkish languages ​​were analyzed on the basis of vocal and consonantism poles. In the introductory part, he noted the periods of historical development of Turkic languages, gave information about the Ural-Altaic language family and listed their distinctive features from Indo-European languages. In addition, the names of the states where Turkish languages ​​and dialects are spoken are mentioned. The article also includes the classification of vowels and a brief explanation of consonant sounds. The third direction of the discussion is the explanation of some common words included in the lexicon of Turkish languages.`